Business strategy formulation for ku ka to gain competitive advantage in e-commerce industry - Ramadhan, Mochamad; Fajarindra Belgiawan, Prawira (The Indonesian Journal of Business Administration, 2018)
Abstract. E-commerce is a process of buying and selling that occurs between business perpetrators and consumers via online. Nowadays, e-commerce has made it easier for people to do shopping without having to bother buying directly from a physical store. However, most of e-commerce platforms in Indonesia are B2C platforms that provide various products made from abroad, especially China Due to this circumstance, Ku Ka as one of the e-commerce platforms in Indonesia decided to start its own operations in 2015 on a social business model basis that only sells Indonesian products as a differentiator among other e-commerce platforms and has a noble purpose to help the local business perpetrators and SMEs in Indonesia. This study aims to analyze the current condition of the e-commerce industry and propose a new competitive strategy for Ku Ka to improve its competitiveness. There are four questions that are discussed and answered during this research. The first question is “what is the current condition in the e-commerce industry?” Second, “what are the current Ku Ka business strategies?” The third one is “what are the best competitive strategies for Ku Ka?” and the last one is “what other features that need to be implemented in Ku Ka’s platform?” The external analysis needs to be conducted on this research in order to define the level of external opportunities and threats faced by Ku Ka in the e-commerce industry, while internal analysis is conducted to review resources, strengths, and weaknesses of Ku Ka itself within the company. In addition, TOWS Matrix and Five Diamond Strategy are useful for formulating alternatives and solutions that need to be implemented inside Ku Ka in order to improve its competitiveness. Furthermore, the author formulates a series of business solutions by focusing on three main dimensions, which are Features & Technology, Partnerships, and Campaign.Keywords: e-commerce, Ku Ka, competitive strategy, online shopping, online retailer.